1965
DOI: 10.1083/jcb.27.2.337
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF ACTIDIONE ON MITOSIS IN THE SLIME MOLD PHYSARUM POLYCEPHALUM

Abstract: Actidione, reportedly a specific inhibitor of protein synthesis, was found to reduce the incorporation of labeled amino acids into proteins of the slime mold Physarum polycephalum without drastically inhibiting the incorporation of nucleic acid precursors into RNA. This inhibitor was found to completely block the ensuing mitosis if it was added at any time between telophase and late prophase. Plasmodia given Actidione in late prophase (about the time of nucleolar dissolution) went on through telophase to recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
16
0

Year Published

1966
1966
1990
1990

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 15 publications
4
16
0
Order By: Relevance
“…In a previous communication, actidione (cycloheximide), an antibiotic inhibitor of protein synthesis, was observed to block amino acid incorpora-tion into protein without inhibiting as markedly incorporation of nucleic acid precursor into RNA (3). Frior publications showed that actidione inhibited protein synthesis in a number of organisms by preventing the transfer of activated amino acids to the growing peptide chain (24,27).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous communication, actidione (cycloheximide), an antibiotic inhibitor of protein synthesis, was observed to block amino acid incorpora-tion into protein without inhibiting as markedly incorporation of nucleic acid precursor into RNA (3). Frior publications showed that actidione inhibited protein synthesis in a number of organisms by preventing the transfer of activated amino acids to the growing peptide chain (24,27).…”
Section: Introductionmentioning
confidence: 99%
“…In the slime mould, Physarum polycephalum, cycloheximide added between telophase and nucleolus dissolution in prophase completely blocked the ensuing mitosis (Cummins, Brewer, and Rusch 1965). Cycloheximide does not appear to accumulate any mitotic stages in some mammalian cells, cells blocking in G2 Verbin and Farber 1967).…”
mentioning
confidence: 99%
“…This possibility needs direct confirmation. It is well established that there is little protein or RNA synthesis in metaphase and anaphase (Prescott and Bender 1962;Davidson 1964;Das, Siegel, and Alfert 1965;Hodge, Robbins, and Scharff 1969), but this does not preclude the synthesis of important proteins at prophase (Cummins, Brewer, and Rusch 1965;Cummins, Blomquist, and Rusch 1966;Tobey, Petersen, Anderson, and Puck 1966;Sisken and Wilkes 1967) or telophase. Parchman and Stern (1969) have shown that cycloheximide inhibits protein synthesis in meiotic prophase of lily microsporocytes.…”
mentioning
confidence: 99%
“…In some cells the inhibition of protein syithesis occurs MONTES by inhibition of the trar-isfer of amino acid from soluble RNA to the ribosomes and their subsequent polymerization into protein (Siegel & Sisler 1964). Interestingly, in other cells cyclobeximide produees a blockage of mitosis at early pr-ophase but nol in late propbase or (bereafler (Cummins et al 1965) so cells whicb are in this stage continue the process of mitosis.…”
mentioning
confidence: 99%
“…For example, cyclobeximide markedly inhibits the synthesis of protein (Siegel & Sisler 1964, Bennett et al 1964, Ennis & Lubin 1964, Cummins et al 1965) and DNA (Bennett ct al. 1964, Ennis & Lubin 1964.…”
mentioning
confidence: 99%